Big data in the healthcare system: a synergy with artificial intelligence and blockchain technology - Reyes-González, Juan Pablo; Díaz-Peregrino, Roberto; Soto-Ulloa, Victor; Galvan-Remigio, Isabel; Castillo, Paul; Ogando-Rivas, Elizabeth (Journal of integrative bioinformatics, 2022)
In the last decades big data has facilitating and improving our daily duties in the medical research and clinical fields; the strategy to get to this point is understanding how to organize and analyze the data in order to accomplish the final goal that is improving healthcare system, in terms of cost and benefits, quality of life and outcome patient. The main objective of this review is to illustrate the state-of-art of big data in healthcare, its features and architecture. We also would like to demonstrate the different application and principal mechanisms of big data in the latest technologies known as blockchain and artificial intelligence, recognizing their benefits and limitations. Perhaps, medical education and digital anatomy are unexplored fields that might be profitable to investigate as we are proposing. The healthcare system can be revolutionized using these different technologies. Thus, we are explaining the basis of these systems focused to the medical arena in order to encourage medical doctors, nurses, biotechnologies and other healthcare professions to be involved and create a more efficient and efficacy system.
Gesehen am 22.04.2024